INNOVATIVE APPROACHES AND PEDAGOGICAL STRATEGIES FOR DEVELOPING ORAL ENGLISH LANGUAGE SKILLS IN VISUALLY IMPAIRED STUDENTS THROUGH AUDIO-BASED TOOLS - Dildora Muslimova (Bright Mind Publishing, 2025)
This article explores innovative approaches and pedagogical strategies for enhancing oral English language skills in visually impaired students through audio-based tools. Traditional language learning practices often rely heavily on visual aids, which limit accessibility for learners with visual impairments. In contrast, audio tools such as podcasts, interactive listening applications, audio dictionaries, and screen readers provide inclusive and effective pathways for skill development. The study highlights how audio-based instruction fosters accurate pronunciation, fluency, and conversational confidence by offering authentic auditory input and repeated practice opportunities. Drawing on theories of inclusive education, communicative competence, and learner autonomy, the article presents effective classroom strategies that integrate audio technologies into teaching practice. Special emphasis is placed on reflective learning, motivation, and the psychological benefits of accessible resources. Findings suggest that adopting innovative, audio-centered pedagogy not only ensures equal learning opportunities but also empowers visually impaired learners to achieve higher levels of communicative competence.
Keywords: Audio tools, oral skills, visually impaired, inclusive pedagogy, pronunciation, fluency, accessibility, motivation.